2022
DOI: 10.1108/ijphm-01-2021-0010
|View full text |Cite
|
Sign up to set email alerts
|

Effect of relationship marketing on hospital loyalty: the mediating role of patient satisfaction

Abstract: Purpose This study aims to reveal the mediating role of patient satisfaction on the impact of relationship marketing on hospital loyalty. Design/methodology/approach The scale questionnaires used in the study was the Relationship Marketing, Hospital Loyalty and the Patient Satisfaction Scale. The population of the study is made up of the patients who received in-hospital services in private hospitals operating in Kocaeli province. The field study was conducted between August 1 and October 31, 2019. After det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 45 publications
1
6
0
Order By: Relevance
“…The results of the study by Yıldırım et al (2022), are in line with research that looks at the influence of relationship marketing on hospital loyalty, it was found that relationship marketing has a positive influence on patient loyalty mediated by patient satisfaction. Furthermore, in line with research that looks at the influence of relationship marketing on consumer loyalty in hospital service businesses.…”
Section: Hypothesissupporting
confidence: 79%
See 2 more Smart Citations
“…The results of the study by Yıldırım et al (2022), are in line with research that looks at the influence of relationship marketing on hospital loyalty, it was found that relationship marketing has a positive influence on patient loyalty mediated by patient satisfaction. Furthermore, in line with research that looks at the influence of relationship marketing on consumer loyalty in hospital service businesses.…”
Section: Hypothesissupporting
confidence: 79%
“…Patients also have the opportunity to choose a health institution amid the large number of health institutions today. For this reason, health institutions are trying to improve themselves to be able to meet expectations and maintain patient loyalty (Yıldırım et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the health-care industry has shifted towards a quality-based care model, as opposed to a volume-based model, to provide high-quality services to their patients. These initiatives have had a significant impact on both patient satisfaction and the health-care industry as a whole, providing a strong foundation for short-and long-term success (Chatterjee et al, 2020;Yıldırım et al, 2022;Thrassou et al, 2023). The present study aims to investigate the reasons why patients use the internet for health-related information and how this affects their interactions with physicians.…”
Section: Relationship Between Variablesmentioning
confidence: 99%
“…Patient satisfaction is now becoming one of the measures of the quality of services provided and a key factor in determining the success of a health facility (Gupta et al, 2022;Ferreira et al, 2020;Lagrosen et al, 2020;Rahman et al, 2021;Yarimoglu, Ataman, 2021;Yoon, Lee, 2022;Martínez et al, 2021;Vieira et al, 2022). According to scientific research, patient satisfaction also affects loyalty to the healthcare facility (Yıldırım et al, 2022).…”
Section: Patient Satisfaction Surveys and Related Workmentioning
confidence: 99%